Inflammatory reaction patterns of the lung as a response to alveolar hypoxia and their significance for the diagnosis of asphyxiation - Gutjahr, Ewgenija; Madea, Burkhard (Forensic science international, 2019)
Providing evidence of asphyxia death is a challenging issue in forensic pathology. Besides helpful macroscopical signs (e.g. strangulation mark, lung edema), recent data from literature indicate that the time of protracted asphyxia suffices to trigger an increase of giant cells and a migration of inflammatory cells from the bone marrow to the lung, thus offering a help in diagnosis of asphyxia death. In search of new valid asphyxia markers, the present study examined this hypothesis and investigated the leading role of pre-existing lung tissue cells and their functional state in reaction patterns to asphyxia. In specimens of suffocated human lungs following a short (n = 13) and a long asphyxia terminal episode (n = 15), and controls (sudden cardiovascular (n = 11) and traumatic deaths (n = 7)), the count of alveolar phagocytes, megakaryocytes, giant and mast cells, using H&E and toluidine blue staining, was performed. To show macrophage activation, immunohistochemical stainings for CD68, late (25F9) and early (MRP-8/-14) stage inflammatory markers were used. Measuring concentration of tryptase in femoral blood acted as a parameter for mast cell degranulation and consequently their activation. Results showed the lack of specificity of macroscopical parameters despite an association of suffocation with heavy lung edema. No significant differences in the numbers of inflammatory cells in the lungs of different case groups were detected. The doubling of MRP-8- and a five-fold elevation of MRP-14-positive cells compared to cardiovascular controls, proved an early activation state of pre-exiting monocytes in protracted asphyxia. These activated monocytes induced the degranulation of mast cells, resulting in slightly elevated tryptase levels in suffocation compared to cardiovascular controls. In summary, the duration of asphyxia (max. 20 min in cases investigated) only suffices to cause changes on molecular level, being not detectable in any specific macroscopical or histological form in the lung. Despite a potential utility of this molecular insight in individual cases, these results point to the classic doctrine of the evaluation of a rounded overall picture, accentuating on the proof of the ligature tool and the marks of suffocation process.
Gesehen am 29.01.2020